Emerging Trends in Clinical Laboratory Automation: Enhancing Efficiency and Accuracy - Hazim Ahmed Yahya Alzahrani; Wael Abdulelah Mufarrih; Anwar Abdullah Saeed Al-Ghamdi; Ahmed Muhammad Ali Al-Ghamdi; Abdullah Ali Alghamdi; Abdulrahman Jamaan Badawi Alghamdi; Ali said Ali abubaker; Abdulelah Mohammed Abdullah; Mohammed Abdullah Ali Alghamdi; Adil Atiya Ali AlGhamdi; Saleh Nahi Saleh Alghamdi (International Journal of Medical Toxicology and Legal Medicine, 2024)
In recent years, clinical laboratory automation has emerged as a pivotal innovation, redefining the landscape of diagnostic testing by enhancing both efficiency and accuracy. This study utilizes secondary data to explore the evolving trends within this domain, offering a comprehensive analysis of technological advancements and their implications for modern laboratories. The research highlights key developments such as the integration of artificial intelligence, machine learning algorithms, and robotic systems, which have collectively optimized workflow processes, reduced human error, and accelerated turnaround times. Furthermore, the study examines the financial and operational benefits realized through automation, including cost-effectiveness and improved throughput. By synthesizing existing literature and data, this study underscores the transformative potential of automation technologies in clinical labs, paving the way for improved patient outcomes and setting new benchmarks in laboratory diagnostics. The insights garnered provide valuable guidance for healthcare institutions aiming to innovate and align with emerging technological trends in the pursuit of superior healthcare delivery.